Pragmatic Development in Foreign Learners of Indonesian - Sitawati,; I Wayan Dana Ardika, I Made Rai Jaya Widanta, Putu Dyah Hudiananingsih, Anak Agung Raka (Opción)
This study was aimed at mapping pragmatic competence development of foreign learners’ of Indonesia. The participants involved were ninety foreign learners of Indonesian in five institutions in Bali who have been learning the language for two semesters. They were grouped into two groups, forty five students were in experiment and the other forty five were in control group. The comparison result showed that students performed better after they have learned Indonesian language for two semesters. It can be implied that teaching Indonesian language should incorporate language content and other aspects, such as Indonesian culture, pragmatic, cross culture understanding, and they should be inserted in syllabus.